Effect of mechanochemical activation on sorption properties of raw minerals - Psareva, T. S.; Zakutevskyy, O. I.; Bachericova, I. V.; Wieczorek–Ciurowa, K. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2008)
An effect has been studied of mechanochemical activation on sorption properties of raw zeolites toward U(VI). Mechanochemical activation was shown to result in the accumulation of structure defects and to increase of vermiculite and apatite surface areas so improving their sorption properties. A mechanochemical activation for 30 min was found to be enough to produce a sorbent with optimum sorption capacity.